Financial assessment of oil palm cultivation on peatland in Selangor, Malaysia - M.N. Noormahayu; A.R. Khalid; M.A. Elsadig (Mires and Peat, 2009)
Oil palm plantations on peat soils are generally believed to have greater environmental impacts than those on other soil types. Nonetheless, Malaysia operates substantial incentives to maximise palm oil production, which in practice encourage the establishment of plantations on peatland. This paper explores the social and economic basis of oil palm cultivation on one peatland estate at Sungai Panjang in the state of Selangor, peninsular Malaysia. Data were obtained by conducting a questionnaire survey of 200 farmers who cultivate oil palm on peat soil. Some of the data were cross-tabulated against farmers’ ages in order to identify any age-related trends in education level, the area of land farmed, annual income and knowledge about oil palm cultivation. The Cobb-Douglas production function was used to model the financial output from oil palm in terms of the costs of chemical inputs and labour. The results indicated that cultivation of this crop gives decreasing returns to scale on peatland in Sungai Panjang, and that chemical inputs are more important than labour cost in determining the level of financial output. Finally, the financial viability of oil palm cultivation for farmers was assessed by calculating three financial indicators (NPV, BCR and IRR). This can be a profitable investment so long as growth conditions, costs, selling price and interest rate do not fluctuate substantially. Greater annual returns can be achieved over 20–25 years than over shorter periods, especially of less than 10 years.